Unbekannte Zeugnisse zu den Leipziger Aufführungen von Felix Mendelssohn Bartholdys Bühnenmusik zur „Antigone“ in den Jahren 1841 und 1842 - Weiss, Hermann F. (Die Musikforschung, 1998)
Felix Mendelssohn Bartholdy's activities in Leipzig and his circle of friends and acquaintances in that city have not yet been fully explored. On the basis of hitherto unknown sources new information is provided concerning the performances of his <Antigone> at the Leipzig Theatre in March, 1842, as well as a performance at the Leipzig home of Johann Paul von Falkenstein on November 28, 1841. The reactions of two Leipzig professors, Moritz Wilhelm Drobisch and Gottfried Hermann, to these events are of particular interest.